Deep Brain Stimulation (DBS) Applications - Tipu Aziz (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The issue is dedicated to applications of Deep Brain Stimulation and, in this issue, we would like to highlight the new developments that are taking place in the field. These include the application of new technology to existing indications, as well as 'new' indications. We would also like to highlight the most recent clinical evidence from international multicentre trials. The issue will include articles relating to movement disorders, pain, psychiatric indications, as well as emerging indications that are not yet accompanied by clinical evidence. We look forward to your expert contribution to this exciting issue.